Strategi Pemasaran Digital Melalui Media Sosial Dalam Penyelengaraan Event Inacraft 2022 - Shelby Dhoz Basnet; Anisatul Auliya (STIE Pariwisata API Yogyakarta, 2022)
Currently, digital marketing through social media has been carried out by various industries, one of it is the MICE industry, such as the INACRAFT 2022 exhibition. In its implementation, to achieved the target of INACRAFT 2022 visitors, need a strategy for the marketing which can run effectively and be able to attract visitors. Therefore, this Final Project examined the digital marketing strategy with social media implemented by PT. Mediatama Binakreasi in organizing the INACRAFT 2022 event. The purpose of this research is to find out digital marketing strategies with social media, the benefits derived from using digital marketing through social media, and the management of social media used in INACRAFT 2022 event. This research using descriptive qualitative research with data collection techniques, namely observation, interviews, and literature studies. The resource persons (interviewee) of this research are Marketing & Communication (Marcomm) Manager, Supervisor, and Social Media Officer from PT. Mediatama Binakreasi. The results of this research indicate that INACRAFT 2022 focuses on digital marketing through INACRAFT's official social media with campaigns using Instagram, Facebook, and Youtube. From this results, expectedly this research can provide useful information in the marketing field, especially digital marketing through social media on the event.